2021
DOI: 10.3390/polym13244327
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Functional Polymer Materials for Energy, Water, and Biomedical Applications: A Review

Abstract: Academic research regarding polymeric materials has been of great interest. Likewise, polymer industries are considered as the most familiar petrochemical industries. Despite the valuable and continuous advancements in various polymeric material technologies over the last century, many varieties and advances related to the field of polymer science and engineering still promise a great potential for exciting new applications. Research, development, and industrial support have been the key factors behind the gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 397 publications
(293 reference statements)
0
14
0
Order By: Relevance
“…The most obvious solution was to exploit the physical, optical, and color changes following radiation treatment. , The most widespread solution was based on composite films whose matrix is an easy-to-cast polymer that interacts with different host molecules without affecting their colorimetric, physical, or optical characteristics. , At present, functional polymers are widely investigated in various fields. Several polymers have been reported as matrices of thin-film dosimeters, such as PVA, nylon-6, polystyrene, polymethyl methacrylate, and polyvinyl chloride. Their possible doping using different dyes preceding their irradiation was studied, and their dosimetric efficiency was evaluated. In line with this, the investigation of PVA-doped films has shown great interest in several studies and research. , PVA has shown more opportunities due to its low cost, availability, nontoxicity, water solubility, and ability to incorporate a wide range of transition metal salts and dyes. Currently, nanofibrous materials via different electrospinning technologies are widely reported and proven effective in various biomedical applications including tissue engineering, wound dressing, drug delivery, regenerative medicine, disease modeling, and detection/biodetection. These sustainable electrospun composites were effective due to their ease of operation, nanoscale diameter, wide specific surface, high porosity, cost-effectiveness, and the considerable adaptability for engineering eco-friendly bioactive nanomaterials. , Electrospun nanomaterials synthesized by mixing high molecular weight polymers and different sensitive dye molecules could be an effective way to prepare various nanomaterials as dosimeters of different γ-ray exposure levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious solution was to exploit the physical, optical, and color changes following radiation treatment. , The most widespread solution was based on composite films whose matrix is an easy-to-cast polymer that interacts with different host molecules without affecting their colorimetric, physical, or optical characteristics. , At present, functional polymers are widely investigated in various fields. Several polymers have been reported as matrices of thin-film dosimeters, such as PVA, nylon-6, polystyrene, polymethyl methacrylate, and polyvinyl chloride. Their possible doping using different dyes preceding their irradiation was studied, and their dosimetric efficiency was evaluated. In line with this, the investigation of PVA-doped films has shown great interest in several studies and research. , PVA has shown more opportunities due to its low cost, availability, nontoxicity, water solubility, and ability to incorporate a wide range of transition metal salts and dyes. Currently, nanofibrous materials via different electrospinning technologies are widely reported and proven effective in various biomedical applications including tissue engineering, wound dressing, drug delivery, regenerative medicine, disease modeling, and detection/biodetection. These sustainable electrospun composites were effective due to their ease of operation, nanoscale diameter, wide specific surface, high porosity, cost-effectiveness, and the considerable adaptability for engineering eco-friendly bioactive nanomaterials. , Electrospun nanomaterials synthesized by mixing high molecular weight polymers and different sensitive dye molecules could be an effective way to prepare various nanomaterials as dosimeters of different γ-ray exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…28 − 30 Currently, nanofibrous materials via different electrospinning technologies are widely reported and proven effective in various biomedical applications including tissue engineering, wound dressing, drug delivery, regenerative medicine, disease modeling, and detection/biodetection. 30 33 These sustainable electrospun composites were effective due to their ease of operation, nanoscale diameter, wide specific surface, high porosity, cost-effectiveness, and the considerable adaptability for engineering eco-friendly bioactive nanomaterials. 34 , 35 Electrospun nanomaterials synthesized by mixing high molecular weight polymers and different sensitive dye molecules could be an effective way to prepare various nanomaterials as dosimeters of different γ-ray exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Functional polymeric materials play a very crucial role in driving progress in the surging quest to acquire renewable energy systems based on electrochemical reactions [ 1 ]. Particularly, these functional materials are widely investigated to develop polymer electrolytes and separators for reliable and sustainable energy conversion and storage devices such as supercapacitors, batteries, electrolyzers, and fuel cells [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are considered a source of natural antioxidant substances, such as polyphenols and polysaccharides [ 12 ]. Thus, reports demonstrated that natural polysaccharides have received increasing attention, due to their diverse biological activities, including antioxidant, antibacterial, antihyperlipidemic, antidiabetic, antiproliferative, and antitumor activities [ 13 , 14 , 15 , 16 ]. They are considered more effective and safe, compared to some synthetic antioxidants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%